In Australia, Most HIV Infections Among Gay and Bisexual Men are Attributable to Sex with ‘New’ Partners - Down, I.; Ellard, J.; Bavinton, B.; Brown, Graham; Prestage, G. (Springer New York LLC, 2017)
© 2017, Springer Science+Business Media New York. It has been estimated that the majority of global HIV infections among gay and bisexual men (GBM) can be attributed to sex within a committed relationship. In Australia, however, negotiated safety, whereby HIV-negative regular partners agree to discard condoms with each other but commit to consistent condom use with other partners, has been promoted as a key component of the HIV prevention response. We asked GBM recently diagnosed with HIV to describe their relationship to the person they believed to be the source of their infection (‘source person’). The majority (66.1%) ascribed their infection to a casual partner. A further 23.3% ascribed their infection to a non-committed and non-romantic partner (or ‘fuckbuddy’). Only 10.6% believed they had acquired their HIV from a ‘boyfriend’ in the context of a committed romantic relationship, and 51.7% of these occurred within the first 3 months following their first sexual contact. Most men (61.5%) believed they had acquired their HIV infection on the first occasion they had sex with the source person. In the Australian context, negotiated safety appears to have minimised infections between regular partners. However, many HIV infections between regular partners may not be in the context of a romantic committed relationship, and yet this distinction between types of regular partners has been all but ignored. Furthermore, in this sample, most infections occurred on the occasion of first meeting, suggesting that the most useful indicators of risk may be the characteristics, contexts, and lengths of sexual partnerships and how sex is negotiated, rather than how GBM categorize their partner. Findings suggest more new HIV infections occur in new partnerships, than in established relationships.